Effects of renin–angiotensin inhibitors on renal function and the clinical course in patients with decompensated cirrhosis - Tammo L. Tergast; Marie Griemsmann; Heiner Wedemeyer; Markus Cornberg; Benjamin Maasoumy (Scientific Reports, 2023)
Abstract Patients with decompensated cirrhosis are at risk of developing acute kidney injury (AKI). Studies have suggested that inhibition of the Renin-Angiotensin System (RAS) has certain nephro- and hepatoprotective effects in patients with compensated liver disease. This study aimed to investigate the clinical impact of RAS-Inhibitors in individuals with decompensated liver cirrhosis. Overall, 1181 consecutive hospitalized patients with ascites that underwent paracentesis were considered for this retrospective study. In total, 667 patients with decompensated cirrhosis fulfilled the inclusion criteria and were finally analyzed. RAS-Inhibitor intake was documented in 41 patients (7%). First, 28-day incidences of AKI and grade III AKI of all patients with RAS-Inhibitors were compared to those without intake. Afterwards, propensity score matching was conducted in a 3:1 manner. Here, incidence of further renal endpoints such as need of hemodialysis were analyzed in detail. In the unmatched setting, intake of RAS-Inhibitors was not associated with an increased 28 day-incidence of AKI (P = 0.76) or LTx-free survival (P = 0.60). However, 28 day-incidence of grade III AKI was significantly lower in patients with RAS-Inhibitor intake (P < 0.001). In the matched setting, 28 day-incidence of AKI did not differ (P = 0.81), while grade III AKI was significantly less frequent in the RAS-Inhibitor group (P < 0.001). Need for hemodialysis was also significantly lower in patients with RAS-Inhibitors (P = 0.03) and LTx-free survival was comparable between both groups (P = 0.52). Thus, this study suggests that intake of RAS-Inhibitors is associated with decreased incidences of grade III AKI and need of hemodialysis in patients with decompensated liver disease.